2014
DOI: 10.1177/0040517514545254
|View full text |Cite
|
Sign up to set email alerts
|

Thermal resistance models of selected fabrics in wet state and their experimental verification

Abstract: This study investigated the structural model of textile fabrics affected by moisture. The model has been verified through five fleece fabrics made up of various textile materials and subjected to several mechanical surface treatment levels. Thermal resistance is one of the key parameters of thermal comfort along with water vapor permeability. In recent times, a keen interest has been focused on the mathematical modelling of this parameter and its experimental verification. However, most of these efforts are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 10 publications
4
30
0
Order By: Relevance
“…This parameter indicates the heat conduction capability of the solid materials and is largely dependent on their structure. 37 Analyzing the results obtained, it was observed that there was an increase in the thermal conductivity in all the finished samples. Considering that the basic textile material was the same, before and after the treatment, the changes registered in this property can be directly attributed to the finishes performed.…”
Section: Thermal Conductivitymentioning
confidence: 95%
“…This parameter indicates the heat conduction capability of the solid materials and is largely dependent on their structure. 37 Analyzing the results obtained, it was observed that there was an increase in the thermal conductivity in all the finished samples. Considering that the basic textile material was the same, before and after the treatment, the changes registered in this property can be directly attributed to the finishes performed.…”
Section: Thermal Conductivitymentioning
confidence: 95%
“…Equation 13 confi rms that as fabric moisture increases, the thermal resistance of a fabric decreases, which causes an increase in the cooling fl ux conducted away from the skin. Th is explanation can be further simplifi ed: an increase in the moisture content of a fabric will likely be followed by an increase in the mass transfer area, at least to some extent.…”
Section: Water Vapour Permeability Of Wet Fabricsmentioning
confidence: 99%
“…Th is original mathematical model for the thermal resistance of single-layer woven wet fabric presented by Mangat et al [13] includes the thermal resistance of dry fi bre polymer segments:…”
Section: Semi-empirical Model Of the Thermal Resistance Of Fabrics Inmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that moisture accumulation within textile fabric strongly affects its thermal comfort sensation [40][41]. Various investigations indicated that the thermal insulation and water vapour permeability of textile fabrics were influenced by moisture content in the fabric [42][43][44][45][46][47][48][49]. Bearing this in mind, it seems reasonable to expect that moisture content in the fabric affects its liquid transfer properties.…”
Section: Introductionmentioning
confidence: 99%